INTEREST FOR SPORT ACTIVITY AT STUDENTS OF THE 1st ACADEMIC YEAR AT FCHPT STU (Fiep Bulletin - online, 2014)
Our work is focused on finding out motion activity interest and to determine body structure of the 1.st academic year students at FCH PT STU in Bratislava (175 men and 388 women). We gained the information by measurement and using questionnaire method that we consequently statistically processed. We created our own questionnaire which was filled in by students at the initial measurement, which was at the beginning of winter term 2012/2013.
Keywords: motion activity; body structure; university students; active; recreational sportsmen; non-sportsmen